2020
DOI: 10.1007/s10980-020-01170-x
|View full text |Cite
|
Sign up to set email alerts
|

Woody plant species diversity as a predictor of ecosystem services in a social–ecological system of southwestern Ethiopia

Abstract: Context Human-dominated landscapes in the tropics need to be managed for biodiversity and the maintenance of ecosystem services (ES). Nevertheless, integrating both biodiversity conservation and ES management remains a challenge. Objectives This study aimed to quantify woody plant species diversity and associated ES in farmland and forests, and investigate the relationship between species and ES diversity. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 97 publications
0
17
0
Order By: Relevance
“…,Labrière et al (2015) surveyed a range of different land use types in a mosaic of vegetation, including areas with swidden agriculture, rubber tapping and logging and found that tree species diversity and ecosystem service production were highest in natural forests. In southwestern Ethiopia,Shumi et al (2021) found that the diversity of ecosystem services was positively related to the diversity of tree species present, a finding that was replicated byHimes et al (2020) in the Pacific Northwest, USA.Similarly,Balvanera et al (2014) summarised evidence indicating a positive relationship between the ecosystem service of timber production and tree species richness. Research undertaken byAlbrich et al (2018) in the Austrian Alps demonstrated a further aspect of this relationship: Tree species diversity had a positive effect on the stability of ecosystem service provision over time.…”
mentioning
confidence: 84%
“…,Labrière et al (2015) surveyed a range of different land use types in a mosaic of vegetation, including areas with swidden agriculture, rubber tapping and logging and found that tree species diversity and ecosystem service production were highest in natural forests. In southwestern Ethiopia,Shumi et al (2021) found that the diversity of ecosystem services was positively related to the diversity of tree species present, a finding that was replicated byHimes et al (2020) in the Pacific Northwest, USA.Similarly,Balvanera et al (2014) summarised evidence indicating a positive relationship between the ecosystem service of timber production and tree species richness. Research undertaken byAlbrich et al (2018) in the Austrian Alps demonstrated a further aspect of this relationship: Tree species diversity had a positive effect on the stability of ecosystem service provision over time.…”
mentioning
confidence: 84%
“…To analyse woody plant diversity, species were grouped into forest specialists, pioneers, and generalists. Data were analysed using constrained correspondence analysis, non-metric multidimensional scaling and generalized linear mixed effects models (Shumi et al 2018(Shumi et al , 2019b(Shumi et al , 2020. Additionally, birds were surveyed in forest (n = 66 sites) and farmland (n = 83 sites), using point counts, and were grouped by ecological traits (Rodrigues et al 2018).…”
Section: Methods Used In the Sub-projectsmentioning
confidence: 99%
“…This specific focus on woody plants was chosen because trees and shrubs are directly used by most local people; other elements of biodiversity may also be useful but not in the same immediate and direct ways (for example, wild mammals are not usually hunted here, unlike in many other parts of Africa). Finally, we combined our data on tree diversity and uses, and used regression modelling to visualise the relationship between woody species diversity and ecosystem services diversity (Shumi et al 2020).…”
Section: Methods Used In the Sub-projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…They support many other species including globally significant populations of birds and mammals and thereby contribute significantly to local biodiversity (e.g., Gove et al 2008;Hylander and Nemomissa 2008). They also contribute to multiple ecosystem services, such as house construction, farm implements, poles and timber, fuel wood, animal fodder, soil fertilization and honey production, that support the livelihoods of local people (e.g., Ango et al 2014;Shumi et al 2021).…”
Section: Introductionmentioning
confidence: 99%